Antioxidant Activity of Zingiber officinale R. Extract Using Pressurized Liquid Extraction Method - Marlon Saldaña-Olguin; Bernardo Junior Quispe-Ciudad; Elza Aguirre (AgriEngineering)
Global food demand is rising, leading to increased food waste, which contains underutilized bioactive compounds. The Pressurized Liquid Extraction (PLE) method employs high temperature and pressure to maintain the solvent in a liquid state above its boiling point, thereby minimizing extraction time and solvent usage. Ginger waste is known to contain bioactive compounds with significant antioxidant activity. We aimed to assess the effect of temperature, time, and particle size on the total phenolic content (TPC) and antioxidant activity (AA) of ginger (Zingiber officinale R.) waste aqueous extract using the PLE method. A Box–Behnken design with 16 runs was employed. Each extraction utilized 40 g of the sample and was conducted at a constant pressure of 20 bar with a solvent ratio of 27:1 mL/g. Data analysis was performed with Minitab® 19.1 (64-bit). TPC ranged from 10.42 to 14.1 mg GAE/g, and AA ranged from 72.9 to 111.9 μmol TE/g. The model explained 81.07% of AA’s total variability. Positive correlation was found between TPC and AA (Pearson’s ρ = 0.58, p < 0.05). The optimized extraction conditions were a temperature of 126 °C, an extraction time of 38 min, and a particle size between 355 and 500 μm. Temperature significantly influenced AA (p < 0.05), while time and particle size were not significant factors. To enhance future research, conducting nutritional and functional studies on the extracted compounds would provide valuable insights. Lastly, evaluating the economic feasibility of using PLE for ginger waste valorization should be considered to support its commercial application.